If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 2b * 4 = 15.65 Reorder the terms for easier multiplication: 3a + 2 * 4b = 15.65 Multiply 2 * 4 3a + 8b = 15.65 Solving 3a + 8b = 15.65 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8b' to each side of the equation. 3a + 8b + -8b = 15.65 + -8b Combine like terms: 8b + -8b = 0 3a + 0 = 15.65 + -8b 3a = 15.65 + -8b Divide each side by '3'. a = 5.216666667 + -2.666666667b Simplifying a = 5.216666667 + -2.666666667b
| m^2-20m-80=5 | | (-2x^3)(-5x)= | | 20=4y+x | | 5.95(14)=210000 | | p=2t+2wfort | | |x-6|=11 | | 3xsquared=17 | | 2u-13-15u+32= | | 3*n+5=20 | | 3x^2-8=83 | | Z-71=55 | | 12a+12= | | 4x-2(3-x)=12 | | -9=n+-8 | | C+C+C+1+4+4-2=37 | | 3(6)+8-6=4(6)-2(6-4) | | 2=a+-7 | | 3*n+10=46 | | 2m+30=T | | 15*10-(4x*4x)=66 | | -5(2t-4)+7t=4t-2 | | 6(6)-6=7(6)+9-6 | | 2y+2=4y+4 | | 4n-0.75=11.25 | | 7-2m=-33 | | 10y+a(a)=11 | | 15*10-x=66 | | 15*10-4x=66 | | solve-(x^3)-(3x^2)-(21x)+48=0 | | 12x+5+3x-7= | | 2c+5=31 | | x+92=x |